2022
DOI: 10.3390/ijms232112776
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Mechanism of Enhanced UV-B Radiation on the Flag Leaf Angle of Rice

Abstract: Leaf angle is an influential agricultural trait that influences rice (Oryza sativa L.) plant type and yield, which results from the leaf bending from the vertical axis to the abaxial axis. UV-B radiation affects plant morphology, but the effects of varying UV-B intensities on rice flag leaves and the underlying molecular, cellular, and physiological mechanisms remain unknown. This experiment aims to examine the effect of natural light and field-enhanced UV-B radiation (2.5, 5.0, 7.5 kJ·m−2) on the leaf angle o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The development of the plant leaf angle is affected by many factors, and hormones play an important regulatory role in the development of the leaf angle 30 , 31 . Therefore, the role of BR in the process of plant leaf angle development and growth is not negligible, and we found that there were 6 DEGs associated with the brassinosteroid biosynthesis pathway by KEGG analysis of DEGs of WT and lpa1 , and one of the genes encoding steroid 5α-reductase found that the oxidative stress resistance of arabidopsis DET2-deficient plants was enhanced, which may be due to physiological stress caused by long-term lack of BRs in plants.…”
Section: Discussionmentioning
confidence: 99%
“…The development of the plant leaf angle is affected by many factors, and hormones play an important regulatory role in the development of the leaf angle 30 , 31 . Therefore, the role of BR in the process of plant leaf angle development and growth is not negligible, and we found that there were 6 DEGs associated with the brassinosteroid biosynthesis pathway by KEGG analysis of DEGs of WT and lpa1 , and one of the genes encoding steroid 5α-reductase found that the oxidative stress resistance of arabidopsis DET2-deficient plants was enhanced, which may be due to physiological stress caused by long-term lack of BRs in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas chlorophyll a is found in the core complex of both photosystems (PSI and PSII), chlorophyll b is found in the PSII antenna system. Thus, an increase in the ratio of chlorophyll a/b shows a higher susceptibility of the complex to UV-B compared to the peripheral antenna complex [48]. Before UV-B irradiation, the chlorophyll ratio was slightly higher in the phyab2 and cry1 mutants (2.2-2.3) than in the WT (2.1).…”
Section: Impact Of Uv-b and Photoreceptor Deficiency On Photosyntheti...mentioning
confidence: 94%
“…UVB radiation reduced the transcript levels of unidentified GA20-oxidase ( GA20ox ) and GA3-oxidase ( GA3ox ) family members involved in gibberellin biosynthesis [ 58 ]. Furthermore, gibberellin and brassinolide have been found to positively control the flag leaf angle under increased UVB radiation [ 59 ], possibly owing to an imbalance in cell division and growth on the adaxial and abaxial surfaces of the lamina [ 60 , 61 ]. The effects of UVB-induced growth inhibition maybe controlled by regulating the gibberellin signaling pathway, which control cell division and elongation.…”
Section: Potential Strategies For Breeding Uvb-resistant Plantsmentioning
confidence: 99%